The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.3389/fnsys.2013.00048
|View full text |Cite
|
Sign up to set email alerts
|

Linking prenatal experience to the emerging musical mind

Abstract: The musical brain is built over time through experience with a multitude of sounds in the auditory environment. However, learning the melodies, timbres, and rhythms unique to the music and language of one’s culture begins already within the mother’s womb during the third trimester of human development. We review evidence that the intrauterine auditory environment plays a key role in shaping later auditory development and musical preferences. We describe evidence that externally and internally generated sounds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 106 publications
0
32
0
2
Order By: Relevance
“…Music may provide a way to deliver structured patterns to the developing brain, which could in turn lead to neurodevelopmental benefits. Even ‘simple music’ such as lullabies are far more structured than the panoply of noise possible in the NICU, and thus might provide a form of early sensory enrichment for the developing brain . Once again, animal studies provide an interesting model.…”
Section: Why Might Music Help?mentioning
confidence: 99%
“…Music may provide a way to deliver structured patterns to the developing brain, which could in turn lead to neurodevelopmental benefits. Even ‘simple music’ such as lullabies are far more structured than the panoply of noise possible in the NICU, and thus might provide a form of early sensory enrichment for the developing brain . Once again, animal studies provide an interesting model.…”
Section: Why Might Music Help?mentioning
confidence: 99%
“…The preferred tempo of music decreases with age and leg length (Drake, Jones, & Baruch, 2000). But since tempo biases and the detection of a regular pulse in an auditory signal can be demonstrated in children from birth, even before walking (Winkler, Haden, Ladinig, Sziller, & Honing, 2009), it has been proposed that movements of the mother may influence such rhythmic behavior more than does the child's own movements (Ullal-Gupta et al, 2013). Newborns distinguish regular features in the acoustic environment despite alteration and they have spectral as well as temporal processing prerequisites of music perception (Winkler et al, 2009).…”
Section: Sound In Uteromentioning
confidence: 99%
“…Other work suggests that music development may also undergo a process of perceptual narrowing . In particular, two infant studies, conducted by Hannon and Trehub, reported the first evidence of perceptual narrowing to musical rhythm.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] Other work suggests that music development may also undergo a process of perceptual narrowing. [22][23][24][25][26][27][28][29][30][31] In particular, two infant studies, conducted by Hannon and Trehub, 23,24 reported the first evidence of perceptual narrowing to musical rhythm. In these studies, the authors tested whether younger and doi: 10.1111/nyas.14050 older Western infants could detect structural violations to the meter of native and nonnative musical rhythms.…”
Section: Introductionmentioning
confidence: 99%